A hybrid inorganic-organic heterojunction device: structural morphology and electrical response - Abdul Rani, Abdul Ismail; Mohamad, Khairul Anuar; Ibrahim, Pungut; Saad, Ismail; Kumar, Ghosh Bablu; Pien, Chee Fuei; Alias, Afishah (Penerbit Uthm, 2019)
Organic-inorganic heterojunctions have a promising future due to their efficient optical and electrical properties, which make them technologically useful for optoelectronics applications. The aim of developing hybrid devices was to combine the significant advantages of each component that forms a heterojunction. It helps to decrease or overcome the drawbacks hindering to achieve the ideal behaviour of synergic effect that results in the development of new systems with new properties. Inorganic semiconductor materials offer a broader absorption of spectrum compared to the organic semiconductors. Their characteristic resemblance to green technology, optical and biocompatible properties presents improvements of response and sensitivity of electronic devices. Wide range resistance, high optical transparency in the visible light region and wide band-gap energy, enhances the application of oxide material for optoelectronics application. Combining such organics semiconductors with inorganics semiconductors of wide optical band-gap is a promising for optoelectronics applications and radio frequency identification (RFID) tags. Investigation of structural morphology and analysis of electrical response are presented to state the device performance based on a hetero-structure device configuration. Keywords: Hybrid inorganic, heterojunction, optical device, inorganic-organic semiconductor